Get personalized answers to your specific questions with IDNLearn.com. Our experts are ready to provide in-depth answers and practical solutions to any questions you may have.
Sagot :
Answer:
Add '-10x' to each side of the equation.
60 + -10x = 10x + -10x
Combine like terms: 10x + -10x = 0
60 + -10x = 0
Add '-60' to each side of the equation.
60 + -60 + -10x = 0 + -60
Combine like terms: 60 + -60 = 0
0 + -10x = 0 + -60
-10x = 0 + -60
Combine like terms: 0 + -60 = -60
-10x = -60
Divide each side by '-10'.
x = 6
Simplifying
x = 6
We appreciate your contributions to this forum. Don't forget to check back for the latest answers. Keep asking, answering, and sharing useful information. Find reliable answers at IDNLearn.com. Thanks for stopping by, and come back for more trustworthy solutions.